Oocyte-inspired universal whole-cell vaccines against tumor heterogeneity - Sishi Guo; Qi Lei; Yun Chen; Junxian Yang; Jiangguo Lin; C. Jeffrey Brinker; Jimin Guo; Wei Zhu (Proceedings of the National Academy of Sciences, 2026)
Tumor heterogeneity poses a major challenge to tumor therapy due to the expression of unique, poorly recognized immunogenic proteins driven by environmental stress. The broad antigenic repertoire of cell-based vaccines, particularly their inclusion of tumor-specific antigens, holds substantial promise for the prevention and treatment of heterogeneous tumors. However, antigen loss during vaccine preparation and insufficient immune activation remain critical challenges for their clinical application. Inspired by the zona pellucida structure of oocytes, an extracellular protective barrier, we developed biomimetic whole-tumor cell vaccines with tunable mechanical properties that preserve the complete repertoire of whole-cell immunogenic proteins. The biomimetic shells optimize cellular mechanics to facilitate phagocytosis and antigen processing, while the cryo-inactivation strategically disrupted intracellular architecture to enhance antigen presentation efficiency. The biomimetic vaccines effectively preserve patient-specific antigen profiles, thereby enabling the generation of tailored immune responses for individualized therapy. Building on the preserved whole-cell antigen pools, we further developed universal vaccines from heterogeneous tumor cells shaped under microenvironmental selective pressures. These vaccines exhibit poly-valent efficacy against tumor heterogeneity, offering considerable potential for both therapeutic and preventive application.